2007
DOI: 10.1037/0021-9010.92.5.1380
|View full text |Cite
|
Sign up to set email alerts
|

Combining predictors to achieve optimal trade-offs between selection quality and adverse impact.

Abstract: The authors propose a procedure to determine (a) predictor composites that result in a Pareto-optimal trade-off between the often competing goals in personnel selection of quality and adverse impact and (b) the relative importance of the quality and impact objectives that correspond to each of these trade-offs. They also investigated whether the obtained Pareto-optimal composites continue to perform well under variability of the selection parameters that characterize the intended selection decision. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(200 citation statements)
references
References 36 publications
4
196
0
Order By: Relevance
“…In a series of papers, DeCorte and colleagues (DeCorte et al 2007(DeCorte et al , 2010(DeCorte et al , 2011 provided an analytic technique that optimizes the goals prescribed by an organization. The various aspects that are entered into the optimization procedure include the predictor subset and its characteristics, the selection ratio or selection rule, the staging and sequencing of the selection procedure, and the weighting of the predictors.…”
Section: Diversity-validity Dilemma and Predictive Biasmentioning
confidence: 99%
“…In a series of papers, DeCorte and colleagues (DeCorte et al 2007(DeCorte et al , 2010(DeCorte et al , 2011 provided an analytic technique that optimizes the goals prescribed by an organization. The various aspects that are entered into the optimization procedure include the predictor subset and its characteristics, the selection ratio or selection rule, the staging and sequencing of the selection procedure, and the weighting of the predictors.…”
Section: Diversity-validity Dilemma and Predictive Biasmentioning
confidence: 99%
“…Also, it is assumed that the job performance and the predictor scores follow a multinormal distribution with the same variance/covariance matrix but a different mean structure in the applicant subpopulations. However, it is noted that essentially the same data and identical distributional assumptions underlie all previous related work on the estimation of the effects of predictor weighing on the balance between selection quality and diversity in both the simple (De Corte et al, ) and the complex selection decision context (Scholarios et al, ). Also, certain aspects of the distributional assumption can be relaxed in that the present method can be adapted to handle situations where the predictor variance/covariance matrix varies across the different applicant subgroups.…”
Section: Discussionmentioning
confidence: 93%
“…If cognitive ability is the most valid predictor of job performance, as is often found, then being less selective on this measure may reduce adverse impact but also will compromise validity (this is more likely to be the case to the extent that job performance is saturated with cognitive ability). For example, De Corte, Lievens, and Sackett (2007) demonstrated that noncognitive ability measures had to be weighted substantially heavier relative to cognitive ability measures before satisfying the 4/5 th s rule. Consequently, expected standardized criterion performance of the selected applicants decreased from .78…”
Section: Methods For Determining the Selection Decision Point The Stmentioning
confidence: 99%